The end of employer-provided health insurance : why it's good for you, your family, and your company - Pilzer, Paul Zane; Lindquist, Richard (Wiley, 2015)
"The future of employer-provided health insurance is a #1 concern for business owners, financial executives and insurance professionals. Existing "health insurance" books focus only on public policy or consumers. Using the techniques outlined in this book, employers and their workers learn to save money on health insurance by migrating from group to individual plans at a total cost that is 20-60% lower for the same coverage (That's a savings of $4,000-$12,000 per year for a family of four). We are at the beginning of a huge transformation in the health insurance industry in which 120 million people are expected to move from group to individual insurance by 2025. Similar to the shift from defined benefit pensions to defined contribution 401(k) plans, the end of employer-provided health insurance will create opportunities for new entrants the way 401(k) plans led to the massive growth of Schwab, Fidelity and Vanguard"--